2019
DOI: 10.1111/jam.14536
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas fluorescens LBUM677 differentially increases plant biomass, total oil content and lipid composition in three oilseed crops

Abstract: Aims Pseudomonas spp. have been widely studied for their plant growth–promoting effects. However, their capacity to promote lipid accumulation in oilseed crops is not well characterized. In this study, we evaluated the effect of Pseudomonas fluorescens LBUM677 on lipid accumulation in three oilseed crops: soybean (Glycine max), canola (Brassica napus) and corn gromwell (Buglossoides arvensis), a plant of high nutraceutical interest for its accumulation of the omega‐3 stearidonic acid. Methods and Results Pot e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The results seem to suggest a confounding effect of sampling time and LBUM677 inoculation on the diversity of the rhizosphere microbiomes. This is in part surprising since a general decrease in the population levels of LBUM677 over time in these conditions was also previously demonstrated ( Jiménez et al, 2020 ). In this context, it would be expected that this reduction in the population levels of LBUM677 would not increasingly impact on the rhizosphere microbiome diversity over time.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The results seem to suggest a confounding effect of sampling time and LBUM677 inoculation on the diversity of the rhizosphere microbiomes. This is in part surprising since a general decrease in the population levels of LBUM677 over time in these conditions was also previously demonstrated ( Jiménez et al, 2020 ). In this context, it would be expected that this reduction in the population levels of LBUM677 would not increasingly impact on the rhizosphere microbiome diversity over time.…”
Section: Discussionmentioning
confidence: 59%
“…A previous study examining the effect of LBUM677 on B. napus, B. arvensis , and G. max has shown that this bacterium is a successful PGPR inoculant. Specifically, LBUM677 can significantly increase seed oil yield and fatty acids content of the three different plants ( Jiménez et al, 2020 ). Additionally, LBUM677 demonstrated certain general plant growth promotion properties, including significantly increasing total plant weight in B. napus and B. arvensis , but not in G. max .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research group has thoroughly examined the plant growth promoting effects of two strains of Pseudomonas species, Pseudomonas fluorescens LBUM677 and Pseudomonas synxantha LBUM223. Previous studies conducted with LBUM677 have shown that in addition to plant growth promotion properties, the bacterium is able to increase seed oil content in various oilseed plants, including in corn gromwell (Buglossoides arvensis), a plant of high nutraceutical interest, under various field settings Filion, 2018, 2019;Jiménez et al, 2020). LBUM223 has demonstrated plant growth promotion properties and has been successful in reducing the symptoms of the bacterial pathogen Streptomyces scabies on potato plants in controlled and field settings (St-Onge et al, 2010Arseneault et al, 2015).…”
Section: Introductionmentioning
confidence: 99%